The Role of Epicardial Adipose Tissue in Systemic Sclerosis: A Clinical and Radiological Analysis - Tezcan, Dilek; Özer, Halil; Topaloğlu, Ömer Faruk; Hakbilen, Selda; Kılınçer, Abidin; Yılmaz, Sema (The European Research Journal, 2026)
Objectives: Systemic sclerosis (SSc) is a chronic autoimmune disorder characterized by progressive fibrosis, vasculopathy, and immune dysregulation, leading to multi-organ involvement. Cardiopulmonary complications are major determinants of morbidity and mortality in SSc. Epicardial adipose tissue (EAT), a metabolically active adipose tissue, has been implicated in systemic inflammation and cardiovascular risk. However, its role in SSc remains poorly understood. This study aims to evaluate the relationship between EAT and SSc patients. Methods: This retrospective cross-sectional study was performed at Rheumatology department between 2020 and 2021. Patients were classified according to the 2013 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria for SSc. Laboratory and radiology results were obtained from the electronic registration database. Data were analyzed and compared between groups. EAT was measured using non-contrast computed tomography (CT), and its correlations with clinical features, inflammatory markers, and thoracic CT abnormalities were evaluated. Results: A total of 229 participants, 157 with SSc and 72 age-matched healthy controls, were included in the study. The mean EAT volume was 171.02±81.84 cm³. Correlation analysis revealed a significant positive correlation between EAT volume and interstitial lung disease (ILD) (r=0.260, P=0.001), C-reactive protein (CRP) levels (r= 0.250, P=0.002), disease duration (r=0.205, P=0.010), and age (r=0.528, P<0.001). ROC analysis showed a moderate discriminatory power of EAT volume with an area under the curve (AUC) of 0.647 (95% CI: 0.564-0.729, P<0.001). Conclusions: Higher EAT volume was observed in SSc patients with ILD, suggesting a possible role of epicardial fat in pulmonary involvement in SSc.